Preventing Firearm Violence Among Victims of Intimate Partner Violence in North Carolina, 2003-2004 - Moracco, Kathryn E. ([Verlag nicht ermittelbar], 2008)
The study examined (1) the scope and nature of firearm possession by Domestic Violence Protective Order (DVPO) defendants, (2) pre- and post-legislation experiences of firearm-related intimate partner violence (IPV) among women applying for Domestic Violence Protective Orders, (3) judges' behaviors specifying firearm-related conditions in DVPOs prior to and following the legislation, and (4) the proportion of and manner in which male DVPO defendants surrendered firearms subsequent to the enactment of the new legislation. Records were extracted for 952 adult women (age 18 and older) seeking relief from a male intimate partner by filing a civil action under North Carolina Statute Chapter 50B in Durham and Wake counties, North Carolina from February 1, 2003, to June 30, 2004, and from their male offenders. Researchers compiled data from three sources: (1) DVPO files, (2) Court Ordered Protection Evaluation (COPE) study, and (3) Criminal background checks. Variables from the DVPO files include demographic information about the plaintiff and defendant, the relationship between the plaintiff and defendant, number of children under 18 in common, incident prompting the DVPO motion, DVPO conditions requested by the plaintiff, ex parte conditions granted including firearm-related restrictions, details of DVPO hearing (e.g. date, presence of attorneys), disposition of the permanent DVPO, conditions of the DVPO, if granted, and the Civil District (CVD) number for that case. Variables from the COPE study include COPE interview information regarding the women's intimate partner violence (IPV) experiences prior to filing for the DVPO (including firearm-related IPV), whether the judge inquired about firearms during the ex parte or DVPO hearings, whether the defendant possessed firearm(s) and whether he surrendered them, women's IPV experiences post-ex parte (including firearm-related IPV), and the CVD number for that case. Variables from the criminal background check include applicable charges (assault on female, communicating threats, violation of DVPO, stalking, other domestic violence related charges, firearm charges, and concealed weapon charges), the associated offense dates, and the existence and scope of other types of charges (i.e. one or more than one additional charges), and the CVD number for that case.